2020
DOI: 10.1038/s41598-020-62194-6
|View full text |Cite
|
Sign up to set email alerts
|

Janus effect of glucocorticoids on differentiation of muscle fibro/adipogenic progenitors

Abstract: Muscle resident fibro-adipogenic progenitors (FAPs), support muscle regeneration by releasing cytokines that stimulate the differentiation of myogenic stem cells. However, in non-physiological contexts (myopathies, atrophy, aging) FAPs cause fibrotic and fat infiltrations that impair muscle function. We set out to perform a fluorescence microscopy-based screening to identify compounds that perturb the differentiation trajectories of these multipotent stem cells. From a primary screen of 1,120 FDA/EMA approved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…In contrast, in mature adipocytes, DEX treatment decreases the expression of PPARG2 , SREBP1C , C/EBPα , and FABP4, indicating a decrease in anabolic pathways while increasing lipolysis (increased expression of lipases LIPE , ATGL , MGLL ) and decreasing glucose uptake [ 92 ] ( Figure 2 ). More recently, a study demonstrated that GC can either induce or inhibit the adipogenic differentiation program of muscle-resident fibro-adipogenic progenitors depending on the cellular concentration in cAMP [ 95 ]. Moreover, the inhibitory effects of GC-bound GR on adipogenesis were mediated through the up-regulation of a known GR target: GILZ .…”
Section: Long-term Glucocorticoid Exposure and Insulin Resistance mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in mature adipocytes, DEX treatment decreases the expression of PPARG2 , SREBP1C , C/EBPα , and FABP4, indicating a decrease in anabolic pathways while increasing lipolysis (increased expression of lipases LIPE , ATGL , MGLL ) and decreasing glucose uptake [ 92 ] ( Figure 2 ). More recently, a study demonstrated that GC can either induce or inhibit the adipogenic differentiation program of muscle-resident fibro-adipogenic progenitors depending on the cellular concentration in cAMP [ 95 ]. Moreover, the inhibitory effects of GC-bound GR on adipogenesis were mediated through the up-regulation of a known GR target: GILZ .…”
Section: Long-term Glucocorticoid Exposure and Insulin Resistance mentioning
confidence: 99%
“…Moreover, the inhibitory effects of GC-bound GR on adipogenesis were mediated through the up-regulation of a known GR target: GILZ . Indeed, under antiadipogenic conditions, GILZ is known to bind PPARG2 and inhibit its expression in mesenchymal stem cells (MSCs) [ 95 ]. Overall, GCs increase but are not necessary to the recruitment of progenitor cells towards adipogenesis, while decreasing insulin sensitivity in mature cells, mirroring what can be observed in vivo [ 70 , 92 ].…”
Section: Long-term Glucocorticoid Exposure and Insulin Resistance mentioning
confidence: 99%
“…Muscles of the mdx mouse develop ectopic adipose tissue only in old animals 20 . However, when cultured ex vivo in the absence of the anti-adipogenic signals of the muscle niche, freshly isolated FAPs from young mdx mice readily differentiate into adipocytes 42 . We asked whether the micro-heterogeneity in the expression of SCA-1 has any impact on the ex vivo adipogenic potential.…”
Section: Resultsmentioning
confidence: 99%
“…To rule out the possibility that the observed differences in the adipogenic differentiation of FAP cell states could be a consequence of a different kinetics in reaching cell confluence, we plotted the total number of nuclei per field over the total number of adipocytes per field from the experiment in Fig. 3a–d and we calculated the trend lines 42 . Even though the trend line of SCA1-High-FAPs clearly reveals a correlation between cell confluence and adipogenic differentiation, the trend of SCA1-Low-FAPs shows no increment of adipocytes at increasing nuclei number (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in addition to their pro-regeneration role, in pathological conditions, FAPs are responsible for the development of ectopic intramuscular adipose (IMAT) or connective tissues (IMCT) [16,18,19,23]. Several molecular cues have been reported to be involved in the modulation of FAP differentiation in vitro [15,[24][25][26][27][28][29][30]. However, their relative importance in physiology and pathology remains to be established.…”
Section: Introductionmentioning
confidence: 99%